Mortality by age, gene and gender in carriers of pathogenic mismatch repair gene variants receiving surveillance for early cancer diagnosis and treatment: a report from the prospective Lynch syndrome database. (April 2023) - Dominguez-Valentin, Mev; Haupt, Saskia; Seppälä, Toni T.; Sampson, Julian R.; Sunde, Lone; Bernstein, Inge; Jenkins, Mark A.; Engel, Christoph; Aretz, Stefan; Nielsen, Maartje; Capella, Gabriel; Balaguer, Francesc; et al.
Summary: Background: The Prospective Lynch Syndrome Database (PLSD) collates information on carriers of pathogenic or likely pathogenic MMR variants ( path_MMR ) who are receiving medical follow-up, including colonoscopy surveillance, which aims to the achieve early diagnosis and treatment of cancers. Here we use the most recent PLSD cohort that is larger and has wider geographical representation than previous versions, allowing us to present mortality as an outcome, and median ages at cancer diagnoses for the first time. Methods: The PLSD is a prospective observational study without a control group that was designed in 2012 and updated up to October 2022. Data for 8500 carriers of path_MMR variants from 25 countries were included, providing 71, 713 years of follow up. Cumulative cancer incidences at 65 years of age were combined with 10-year crude survival following cancer, to derive estimates of mortality up to 75 years of age by organ, gene, and gender. Findings: Gynaecological cancers were more frequent than colorectal cancers in path_MSH2, path_MSH6 and path_PMS2 carriers [cumulative incidence: 53.3%, 49.6% and 23.3% at 75 years, respectively]. Endometrial, colon and ovarian cancer had low mortality [8%, 13% and 15%, respectively] and prostate cancers were frequent in male path_MSH2 carriers [cumulative incidence: 39.7% at 75 years]. Pancreatic, brain, biliary tract and ureter and kidney and urinary bladder cancers were associated with high mortality [83%, 66%, 58%, 27%, and 29%, respectively]. Among path_MMR carriers undergoing colonoscopy surveillance, particularly path_MSH2 carriers, more deaths followed non-colorectal Lynch syndrome cancers than colorectal cancers. Interpretation: In path_MMR carriers undergoing colonoscopy surveillance, non-colorectal Lynch syndrome cancers were associated with more deaths than were colorectal cancers. Reducing deaths from non-colorectal cancers presents a key challenge in contemporary medical care in Lynch syndrome. Funding: We acknowledge funding from the Norwegian Cancer Society, contract 194751-2017.